2020
DOI: 10.1101/2020.12.04.412163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homeostatic Synaptic Scaling Establishes the Specificity of an Associative Memory

Abstract: Accurate memory formation has been hypothesized to depend on both rapid Hebbian plasticity for initial encoding, and slower homeostatic mechanisms that prevent runaway excitation and subsequent loss of memory specificity. Here, we tested the role of synaptic scaling in shaping the specificity of conditioned taste aversion (CTA) memory, a Hebbian plasticity-dependent form of associative learning. We found that CTA memory initially generalized to non-conditioned tastants (generalized aversion), becoming specific… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 71 publications
(121 reference statements)
2
7
0
Order By: Relevance
“…Consistent with studies in the hippocampus (Graves et al, 2016), we found that the percentage of BS LIV-VI aIC-BLA projecting neurons in the sampled population was highest in the context of novel taste learning (Extended Figure 1 (Dunn et al, 2018). Indeed, the ratio of BS:RS LIV-VI aIC-BLA neurons was progressively suppressed by familiarity acquisition (Saccharin 1x> 2x> 5x), as well as following aversive taste memory recall (CTA retrieval), compared to both appetitive learning Changes in the intrinsic properties of neuronal ensembles have recently been suggested to contribute to homeostatic mechanisms integrating both cellular and synaptic information (Wu et al, 2021). In our current study, we randomly sampled from neuroanatomically defined LIV-VI aIC-BLA projecting neurons, and even following spike sorting (Extended Figures 1-2), the probability of recording from engram cells (10% of neurons within a region) would be extremely low (Tonegawa et al, 2015).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Consistent with studies in the hippocampus (Graves et al, 2016), we found that the percentage of BS LIV-VI aIC-BLA projecting neurons in the sampled population was highest in the context of novel taste learning (Extended Figure 1 (Dunn et al, 2018). Indeed, the ratio of BS:RS LIV-VI aIC-BLA neurons was progressively suppressed by familiarity acquisition (Saccharin 1x> 2x> 5x), as well as following aversive taste memory recall (CTA retrieval), compared to both appetitive learning Changes in the intrinsic properties of neuronal ensembles have recently been suggested to contribute to homeostatic mechanisms integrating both cellular and synaptic information (Wu et al, 2021). In our current study, we randomly sampled from neuroanatomically defined LIV-VI aIC-BLA projecting neurons, and even following spike sorting (Extended Figures 1-2), the probability of recording from engram cells (10% of neurons within a region) would be extremely low (Tonegawa et al, 2015).…”
Section: Resultsmentioning
confidence: 96%
“…Changes in the intrinsic properties of neuronal ensembles have recently been suggested to contribute to homeostatic mechanisms integrating both cellular and synaptic information (Wu et al, 2021). In our current study, we randomly sampled from neuroanatomically defined LIV-VI aIC-BLA projecting neurons, and even following spike sorting (Extended Figures 1-2), the probability of recording from engram cells (10% of neurons within a region) would be extremely low (Tonegawa et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the entire mEPSC amplitude distribution is thought to be regulated by a multiplicative scaling factor during inactivity 24 , we tested whether the increase in postsynaptic strength in each of our experimental conditions increases according to a multiplicative scaling rule. We used the rank-order method to test for synaptic scaling of mESPC amplitudes in populations of neurons 4,8,31 . To do this, mEPSCs from control and treatment groups (TTX, hibernation, hibernation+TTX, hibernation+nimodipine) were rank-ordered from the smallest to largest amplitude, plotted against each other (ranked control vs. ranked treatment), and fit with a linear regression (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%